Pergeseran Motivasi Haji pada Masyarakat Di Kelurahan Lontar Surabaya - Fransisca Aprillia; Agus Machfud Fauzi (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
Abstract: In the modern era like today, the values ​​that exist in society have shifted, including the value of Hajj. In the past, the motivation for carrying out the pilgrimage was to get closer to Allah while carrying out the fifth pillar of Islam. However, currently the motivation for the pilgrimage is more directed at the value of symbols that serve to raise one's social status in society. This study aims to explore how the shift in motivation for Hajj in the community in Lontar Surabaya Village. Therefore, the theory used in this study is the social construction of Peter L Berger's perspective. This research uses qualitative research with descriptive qualitative approach. The results of this study indicate that; First, the motivation for Hajj in the modern era has shifted, because the social structure of the Lontar community creates a social order that a community group wants to achieve. As a result, the social structure has implications for the shift in Hajj motivation. Second, the shift in motivation for Hajj in the Lontar community is driven by internal and external factors. The internal motivation of the Lontar community to carry out the pilgrimage is to show their high social status in the community. Meanwhile, the external motivation of the Lontar community to carry out Hajj is to increase prestige and get awards in the community.